Student Wellbeing in Higher Education: The Role of Stressors, Student Identity, and Social Support - Milena W Pszczolinska; Kenneth I Mavor; Paula J Miles (SAGE Open)
University student populations are often characterised by low levels of subjective wellbeing. To understand student wellbeing from the social perspective, this study aimed to explore the prediction of wellbeing by social factors over and above the effects of stress. A particular focus was placed on the impact of social support from different sources, but also on the effects of social identification with students in one’s academic-discipline and university, and the impact of incompatible social identities at home and on campus. A sample of university students ( n  = 321) completed an online survey comprising measures of academic-discipline social identification (with one’s discipline and university), social identity incompatibility, stress experienced from negative life events as well as two measures of subjective wellbeing. The conducted analyses suggested that social support drawn from friends and family predicted more positive wellbeing, while support from a significant other did not. Moreover, this relationship mediated the positive impact of university identification on wellbeing, but the same was not found for discipline identification. Identity incompatibility predicted poorer wellbeing and was correlated with lower perceived social support and perceptions of higher experienced stress, which suggests a crucial role of this factor in predicting student wellbeing. The obtained results carry multiple implications for further understanding of the relationship between the three social processes, different forms of stress and student wellbeing, but also to existing preventative strategies which address the social dimension of the student experience.